Beauty is not simplicity: an analysis of mathematicians' proof appraisals - Matthew Inglis; Andrew Aberdein (2014)
What do mathematicians mean when they use terms such as 'deep', 'elegant', and 'beautiful'? By applying empirical methods developed by social psychologists, we demonstrate that mathematicians' appraisals of proofs vary on four dimensions: aesthetics, intricacy, utility, and precision. We pay particular attention to mathematical beauty and show that, contrary to the classical view, beauty and simplicity are almost entirely unrelated in mathematics.